2020
DOI: 10.3390/molecules25102280
|View full text |Cite
|
Sign up to set email alerts
|

Trinuclear NiII-LnIII-NiII Complexes with Schiff Base Ligands: Synthesis, Structure, and Magnetic Properties

Abstract: The reaction of the Schiff base ligand o-OH-C6H4-CH=N-C(CH2OH)3, H4L, with Ni(O2CMe)2∙4H2O and lanthanide nitrate salts in a 4 : 2 : 1 ratio lead to the formation of the trinuclear complexes [Ni2Ln(H3L)4(O2CMe)2](NO3) (Ln = Sm (1), Eu (2), Gd (3), Tb (4)). The complex cations contain the strictly linear NiII-LnIII-NiII moiety. The central LnIII ion is bridged to each of the terminal NiII ions through two deprotonated phenolato groups from two different ligands. Each terminal NiII ion is bound to two ligands in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…Previously we have reported the trinuclear complexes [Ni 2 Ln(H 3 L) 4 (O 2 CMe) 2 ](NO 3 ) (Ln III = Sm, Eu, Gd, Tb), which were isolated by the 4: [19]. The crystal structure of the {Ni 2 Tb} complex revealed that the Tb III ion is linked to each of the Ni II ions via two O phenolato atoms of the (H 3 L) − ligands and contains a strictly linear Ni II -Tb III -Ni II moiety.…”
Section: Synthesis and Ir Spectroscopic Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously we have reported the trinuclear complexes [Ni 2 Ln(H 3 L) 4 (O 2 CMe) 2 ](NO 3 ) (Ln III = Sm, Eu, Gd, Tb), which were isolated by the 4: [19]. The crystal structure of the {Ni 2 Tb} complex revealed that the Tb III ion is linked to each of the Ni II ions via two O phenolato atoms of the (H 3 L) − ligands and contains a strictly linear Ni II -Tb III -Ni II moiety.…”
Section: Synthesis and Ir Spectroscopic Characterizationmentioning
confidence: 99%
“…The last examples indicate that the introduction of chirality in a magnetic system is a probable route to multifunctionality as in the case of transition metal complexes [2]. As the trinuclear mixed 3d/4f metal systems have provided interesting examples with SMM properties [16,17], recently we have focused our research on the Ni II -Ln III -Ni II system [18,19]. In these series of compounds, there are examples which present also SMM properties [20][21][22][23] or the magnetocaloric effect [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 7 Using Schiff base/modified vanillin-based Schiff bases, several multinuclear complexes of d/f block elements have been reported. 8 Notable reports among them are multinuclear dysprosium-based clusters reported by Murugesu et al, who synthesized a series of tetranuclear butterfly core-containing dysprosium clusters, and the magnetic measurements revealed that some of these clusters displayed a high energy barrier for reversal of magnetization. 9 In this backdrop, Schiff-base ligands have been used for synthesizing zinc-based multinuclear clusters, some of which have shown interesting applications as polymerization catalysts, 10 reagents in organic synthesis, 11 molecular precursors for ZnO-based materials, 12 models of the active site in zinc enzymes, 13 and in synthesizing functional molecule-based materials.…”
Section: Introductionmentioning
confidence: 99%